Combating Poverty and Social Inequality in 2023 a Global Imperative for Equitable Development and Social Justice - Ruhana, Faria; Nasution, Muhammad Syafril; Susniwan; Ardieansyah; Sutiapermana, Aden (International Journal of Science and Society, 2024)
In the last decade, poverty and social inequality have become increasingly pressing global challenges, exacerbated by the impact of the global economy, climate change, and the digital revolution. Rising inequality and unequal distribution of wealth not only hinder economic growth but also give rise to social and political instability. The fight against this problem requires a deep understanding of its causal factors and impact on global development. This research aims to analyze the factors that cause poverty and social inequality and their impact on global development, with a focus on solutions to overcome these problems. The research methodology uses a descriptive qualitative approach, with data obtained from relevant literature studies and in-depth analysis of the phenomenon. Data was collected from previous research results and processed through qualitative analysis to build a comprehensive understanding. The research results show that global economic factors, climate change, technology, public policy, and socio-cultural factors are the main causes of poverty and inequality. Its impact on global development includes stunting economic growth, social instability, and reduced access to health and education services. This research also finds that the solution to this problem requires international cooperation, innovative policies from governments, active contributions from the private sector, and the participation of non-governmental organizations. A multidisciplinary and participatory approach, as well as the use of technology and innovation, is needed to create sustainable solutions. Overall, this research provides new insights into strategies for achieving more inclusive and equitable development amidst current global challenges.